PENGARUH MODIFIKASI PERMAINAN TERHADAP HASIL BELAJAR LOMPAT JAUH GAYA WALKING IN THE AIR (STUDI PADA SISWA KELAS X SMA NEGERI 1 GEGER MADIUN) - CRISTANTO, IRFAN (Jurnal Pendidikan Olahraga dan Kesehatan, 2013)
Abstract Physical education and health has very important role to increase the quality of human resources. Whether the education is successful or not depends on the goodness of the disectional education as according to existing order. In school environment there are many problems that need serious intentions, one of them is learning process. In SMA Negeri 1 Geger, Madiun in teaching the basic motion is not coupled with games. This will have an impact on the lack of movement of the student. It is expected that students will be interested in modified game to follow the course of learning and improve learning result. The purposes of this research are (1) to know the effect of modifying the game to the learning result of the walking in the air long jump style in tenth grade of SMA Negeri 1 Geger, Madiun. (2) to know the effect of modified game to the learning result of the walking in the air long jump style in the tenth grade of SMA Negeri 1 Geger, Madiun. This research is a descriptive quantitative with experimental approach. The sample of this study amounted to 64 students, the experimental group class was XC totaling 32 students and the control group class was XB totaling 32 students. From the results can be concluded that there is significant influence of modified game to the learning result of walking in the air long jump style in tenth grade of SMA Negeri 1 Geger, Madiun as evidenced from the tcount 10,6 > ttable 2,0315 with a significance level of 0.05. The influence is 27.18%. Keyword : Modification of the game, learning result, walking in the air long jump style